Effectiveness of Group Guidance Using Problem Solving Technique to Improve Self-Adjustment in Adolescent Students - Ulfa Danni Rosada; Wina Apriyani (Universitas Muhammadiyah Enrekang, 2024)
Students who are adjusting themselves have obstacles or barriers faced by individuals characterized by an attitude of not respecting teachers and friends, acting as they please, not doing assignments, and committing violations in the school environment. One effort that can be made to improve the ability to adjust can be done with group guidance using problem solving techniques. The purpose of this study was to determine the effectiveness of group guidance services using problem solving techniques to improve adjustment in high school students in grade X. This type of research is an experiment with a Pretest-Posttest Control Group Design research design. The population of this study was 213 students in grade X of SMA Negeri 1 Jalaksana, sampling was carried out using the Random Sampling technique. The research sample consisted of 16 students consisting of 8 students in the control group and 8 students in the experimental group. The research instrument was in the form of a scale of adjustment given during the pretest and posttest. The analysis used the two-sample t-test formula. The data was first tested for analysis prerequisites, namely normality and homogeneity tests. The results of the hypothesis using the independent t-test showed sig. (2-tailed) of 0.002 < 0.05, so the research results show that there is a difference in the effectiveness of using group guidance services using problem solving techniques and group guidance services using discussion techniques on students' self-adjustment.